Neurological Outcome of Endoscopic Transsphenoidal Pituitary Tumor Resection Using the Neuronavigation System - Abdul Bari, Shafaat Hussain, Muhammad Ali, Muhammad Assad Javed, Syeda Khoula Azmat, Rakhshinda Younus (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pituitary adenomas can cause substantial neurological and hormonal deficits because of their location and secretory properties. The surgical treatment is now mostly performed using endoscopic transsphenoidal resection due to its lower invasiveness and quicker recovery time. The implementation of neuronavigation systems into these techniques is directed towards enhanced surgical accuracy and improved perioperative results, though information targeting specifically postoperative neurologic enhancement is scant. Assess the stated above objectives concerning the neurological and endocrinological changes after transsphenoidal resection of pituitary tumors performed under neuronavigation. Methods: This prospective observational study was conducted at the department of neurosurgery PAEC General Hospital, Islamabad during March 2022 to November 2022. Fifty eight patients with pituitary adenomas underwent neuronavigation-assisted endoscopic resection. Preoperative assessments included neurological examination, endocrine profiling, and MRI scans. Postoperative outcomes were evaluated based on symptom improvement, hormonal normalization, and MRI findings at follow-up. Results: The mean age of the patients was 42.6 years, with a male predominance (58.6%). Visual impairment and headache were the most common presenting complaints. Gross total resection was achieved in 74.1% of cases. Significant improvements were observed in visual function (58.6%) and headache resolution (67.2%). Hormonal normalization was achieved in 50% of patients with preoperative dysfunction. Postoperative complications were minimal, with low rates of CSF leak (5.2%) and transient diabetes insipidus (12.1%). Residual tumor was detected in 19% of patients on follow-up imaging. Conclusion: Neuronavigation-assisted endoscopic transsphenoidal surgery is a safe and effective approach for managing pituitary adenomas. The technique offers favorable neurological and hormonal outcomes, with low complication rates and a high rate of gross total resection. Its use is particularly beneficial in complex or invasive tumors, enhancing surgical accuracy and postoperative recovery. Keywords: Pituitary adenoma, Endoscopic surgery, Neuronavigation, Transsphenoidal approach, Visual outcomes, Hormonal recovery, Neurological improvement